COURAGE IN R. J. PALACIO’S NOVEL WONDER - Tita Assyifa; Muhammad Fatih Suhadi (JOURNAL OF LANGUAGE, 2023)
This research is entitled Courage in R. J. Palacio's Novel Wonder. This study focuses on the types of courage and the factors behind the courageous actions taken by August Pullman as a protagonist in the novel. It examines what actions are considered courageous actions and what factors affect the courageous actions. This study used the qualitative method as the research method because the data is not numerical. The type of data in the study is the text from two data sources, i.e., primary data and secondary data. The primary data source is the novel, and the secondary data source is the related information. The aim of this study is to find out what types of courage are given by the protagonist and what factors cause him to be courageous in the novel. The writers used Dungate’s theory of the six types of courage to classify the types. The study also applied the study conducted by Rate et al. in implicit theories of courage to classify the factors of courageous actions. The result of the study shows that first, the types of courage found in the protagonist are physical courage, social courage, intellectual courage, and emotional courage; second, the factors that can be found in the protagonist are external circumstances, affective, and motivational factors.